(untitled) (Analysis in Theory and Applications, 2017)
The strong type and weak type estimates of parameterized Littlewood-Paley operators on the weighted Herz spaces K^α,p_q (ω_1 ,ω_2) are considered. The boundedness of the commutators generated by BMO functions and parameterized Littlewood-Paley operators are also obtained.